MOTHER TONGUE’S INTERFERENCE IN MANGGARAIAN STUDENTS’ ENGLISH WRITING OF SENIOR HIGH SCHOOLS STUDENTS IN LANGKE REMBONG SUBDISTRICT - Yosefina Jem; Ignasius Semana (Unika Santu Paulus Ruteng, 2018)
The purpose of this writing is to see the common interferences ofmother tongue in students’ English writing, determine the factors cause those interferences and describe the qualityof students’ writing. This research is done through descriptive qualitative method. It was conducted in five senior highschools in Langke Rembong Sub district. The data for the research were words, phrases or sentences which contain theinterference of Manggarai language in students’ writing. In doing the research, the researchers used some instrumentsto collect the data. Those instruments are questionnaire and students’ task. After collecting the data, the researchersanalyzed the data by doing some procedures: (a) identify the common interferences in students’ writing by comparingstudents writing version to the correct English version; (b) identify the common interferences in students’ writing; (c)describe the common interferences found in students’ writing; (d) determine the factors cause the interference; and(e) describe the quality of students’ writing. The result shows that the common interference occurs in phrase (VP)and tenses (present tense). Those interferences happen because the contribution of students’ environment, narrative situation, cultural ties and lack of English knowledge. Furthermore, those factors of interferences give impact to the quality of students’ writing which is unacceptable. Based on the result of the research, it is very suggested for theteachers of senior high school to provide enough chance for the students to practice English in written form.